OHCHR Policy on the Fulfillment of Aboriginal Rights in Australia - Muhammad Fadhlan (Universitas Warmadewa, 2026)
This study aims to objectively describe human rights violations experienced by the Aboriginal people in Australia and to analyze the role and efforts of the Office of the United Nations High Commissioner for Human Rights (OHCHR) in fulfilling their rights. The analysis in this study uses Galtung peace theory, focusing on OHCHR policies. These policies are then categorized and analyzed based on Galtung three stages of peace: peacebuilding, peacekeeping, and peacemaking. In addition, the concept of positive peace Galtung and Fischer is used to assess the outcomes of OHCHR’s implemented policies. This study uses a qualitative method through a literature study based on secondary data, including books, scholarly journals, reports, and other relevant sources, which are analyzed using data reduction techniques. The findings show that OHCHR has made various efforts to monitor and investigate human rights violations against the Aboriginal people. OHCHR acts based on policy principles to fulfill the rights of the Aboriginal community and to create conditions conducive to humanitarian assistance. One example is through the management of contribution funds from various countries via the UN Voluntary Fund for Indigenous Peoples, where OHCHR serves as the fund's secretariat and supports the implementation of the Expert Mechanism on the Rights of Indigenous Peoples (EMRIP). Although violations still occur, OHCHR is considered to have been fairly successful in carrying out its mandate as a UN body in addressing indigenous rights issues and in supporting the realization of positive peace through its various policies.